2019
DOI: 10.1038/s41598-018-38313-9
|View full text |Cite
|
Sign up to set email alerts
|

The major allergen Der p 2 is a cholesterol binding protein

Abstract: Der p 2 is a major dust mite allergen and >80% of mite allergic individuals have specific IgE to this allergen. Although it is well characterized in terms of allergenicity, there is still some ambiguity in terms of its biological function. Three-dimensional structural analysis of Der p 2 and its close homologues indicate the presence of a hydrophobic cavity which can potentially bind to lipid molecules. In this study, we aimed to identify the potential ligand of Der p 2. Using a liposome pulldown assay, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…But it is speculated that Der p 2 and LPS will strengthen this kind of reaction after forming a complex. However, recent research results show that the natural ligand of Der p 2 is cholesterol, not LPS as previously thought [24].…”
Section: Der Pmentioning
confidence: 78%
“…But it is speculated that Der p 2 and LPS will strengthen this kind of reaction after forming a complex. However, recent research results show that the natural ligand of Der p 2 is cholesterol, not LPS as previously thought [24].…”
Section: Der Pmentioning
confidence: 78%
“…The protein sequence of Blo t 2 also contained the ML domain, which is implicated in lipid recognition 27 . Recently, we have demonstrated that cholesterol is the preferred lipid ligand of Der p 2 44 , but further studies are necessary to identify the lipid ligand and its functional role in Blo t 2.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow to draw conclusion on their contributions in the initiation of the HDM allergic response. The HDM allergens from groups 2,5,7,13,14,21,22,31,35, exhibiting similarities with lipid binding protein and/or showing capacity to interact with lipid cargos, are all susceptible to promote pleiotropic effects on the innate immune system through interactions with TLR2, TLR4 or other receptors as TLR1, TLR6, RAGE, CD14, CD36 (24,28,(58)(59)(60). Whether these proteins play redundant or unique role(s) in the innate immune activation remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%